NMR micro-detectors tailored for multinuclear and electrochemistry lab-on-a-chip applications - Davoodi, Hossein (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2022)
This work offers three solutions tailored to specific applications to overcome NMR challenges in the micro-domain. As the first sub-topic of this work, different potential electrode designs, compatible with NMR technique, are suggested and experimentally evaluated. As the second focus point, this work tackles multinuclear detection challenges. In parallel, a low-cost, broadband insert is discussed to enhance the sensitivity of standard NMR coils when a small sample volume is available.